A Review Onwhole Body Vibrations Towards Human - Ahmad Rasdan, Ismail (2010)
In today’s highly competitive global economy, many organizations are forced to consider more towards their worker’s health performance in order to be competitive. Thus, the understanding of ergonomic is very crucial. In ergonomic, whole-body vibration is one of the most important factors that should be emphasized. There are evidences of a relationship between occupational driver and musculoskeletal disorder,which show that the whole-body vibration could contribute to the musculoskeletal disorderin the occupational driver. Many researchers had published studies on whole-body vibration in developed countriesbut none was done for Malaysian drivers. The main objective of this paper is to carry out a critical analysis of literature review on the effects of whole-body vibration towards human. This study will explain the recent literatures related to the postural, physiological and psychological affected by whole-body vibration. This review would help the researchers, academicians and practitioners to take a closer look on how the vibration will affect Malaysian drivers’ performance especially in the vehicles and transportation industry.